Dynamic event-triggered control for QSR-dissipativity of feedback interconnection of switched nonlinear systems. (May 2023) - Cao, Zhengbao; Zhao, Jun
Abstract: This paper proposes a novel static output feedback based event-triggering mechanism for the feedback interconnection of two switched nonlinear systems with QSR-dissipativity. QSR-dissipativity of such a switched system is illustrated by both multiple storage functions and multiple supply rates. None of subsystems of such a switched system is required to be QSR-dissipative and the increasing case of two adjacent storage functions of subsystems at switching instants is also permitted. For all bounded new inputs belonging to L 2 space, the mechanism without the help of auxiliary conditions of existing literatures can not only guarantee weak QSR-dissipativity of the event-based interconnected systems but also explicitly ensure the nonexistence of Zeno behavior, where the bias term of weak QSR-dissipativity of the event-based interconnected systems can be predetermined. Moreover, the proposed triggering mechanism has also been successfully employed to the feedback interconnection of two non-switched nonlinear systems with QSR-dissipativity. Finally, the effectiveness of the proposed triggering mechanism is illustrated by a numerical example.